Both Hsp70 chaperone and Clp protease plastidial systems are required for protection against oxidative stress. (4th March 2017) - Pulido, Pablo; Llamas, Ernesto; Rodriguez-Concepcion, Manuel
ABSTRACT: Environmental stress conditions such as high light, extreme temperatures, salinity or drought trigger oxidative stress and eventually protein misfolding in plants. In chloroplasts, chaperone systems refold proteins after stress, while proteases degrade misfolded and aggregated proteins that cannot be refolded. We observed that reduced activity of chloroplast Hsp70 chaperone or Clp protease systems both prevented growth of Arabidopsis thaliana seedlings after treatment with the oxidative agent methyl viologen. Besides showing a role for these particular protein quality control components on the protection against oxidative stress, we provide evidence supporting the existence of a yet undiscovered pathway for Clp-mediated degradation of the damaged proteins.